Environmental awareness for patients with COPD undergoing pulmonary rehabilitation: Is it of added value? - Souto-Miranda, Sara (2020)
Chronic obstructive pulmonary disease (COPD) is impacted by exposure to environmental contaminants. Improving health literacy on this topic might help to optimize health outcomes. We aimed to design and deliver a health-education session about the impact of environmental contaminants on respiratory symptoms and explore participants' perceptions on such session. Patients with COPD were recruited from a pulmonary rehabilitation (PR) program. Two focus groups were first conducted to explore knowledge amongst the group. Then, the session was designed and delivered, and three focus groups were conducted to obtain feedback from participants. Data were analyzed thematically by two independent researchers. Thirty-one patients (71 ± 8 years old, FEV1 = 47.6 ± 16.8% predicted; 74.2% male) were included. Prior to the session, participants recognized the importance of this topic and described avoidance strategies to deal with symptom triggering due to air pollution. After the session, participants had their knowledge validated, kept some avoidance strategies, but also adapted some "unavoidable" activities of daily living. Patients with COPD value education on this topic, and PR offers a friendly environment to discuss prevention and management strategies. Contents of the session are provided to help deliver these sessions. Future studies could investigate the effectiveness of this intervention on self-management and exacerbations of COPD.